Retraction Notice for "Pharmacist-strengthen adherence to antiretroviral therapy and the contributing factors among HIV-infected paediatric patients in Nigeria" (Bangladesh Journal of Medical Science, 2017)
Retraction Notice:The article "Pharmacist-strengthen adherence to antiretroviral therapy and the contributing factors among HIV-infected paediatric patients in Nigeria" DOI: http://dx.doi.org/10.3329/bjms.v16i2.31942 was published on April 2017. There was a printing mistake in the authorline which was absolutely unintentional. To avoid any misunderstanding, the Editorial Board of BJSM retracted it on August 2017.